Impact of 5% pentetic acid on the pushout bond strength of AH Plus sealer to dentin: An in vitro study - Gayatri Nitin Patil; Dipali Yogesh Shah; Ashwini Manish Dadpe; Sneha Rajendra Dole; Budhabhushan Ashruba Sonvane; Neeraj Eknath Kolge (Wolters Kluwer Medknow Publications, 2021)
Introduction: The aim of this study was to compare the effect of pentetic acid (diethylenetriaminepentaacetic acid) with ethylenediaminetetraacetic acid (EDTA), as final chelating agents on the pushout bond strength of AH Plus sealer. Materials and Methods: Single-rooted mandibular premolars (n = 80) were collected. The canals were instrumented and were randomly divided into four groups (n = 20) according to the final irrigation protocol followed, where Group I: distilled water, Group II: 3% NaOCl and distilled water final rinse; Group III: 3% NaOCl and 17% EDTA as final irrigant, and Group IV: 3% NaOCl and 5% pentetic acid as final irrigant. Canals were then dried and filled with AH Plus sealer. Roots were sectioned transversely at 4 mm from apex, with 1 mm thickness, and tested for pushout bond strength. Results were analyzed using analysis of variance and post hoc Tukey's test. Results: Pushout bond strength of AH Plus was found to be best with 5% pentetic acid final rinse (0.841 ± 0.15 MPa), followed by 17% EDTA (0.83 ± 0.27 MPa), 3% NaOCl (0.68 ± 0.16 MPa), and distilled water (0.52 ± 0.04). However, there was no statistical difference between 5% pentetic acid and 17% EDTA when used as a final rinse (P < 0.05). The failure modes in Groups III and IV were mixed, whereas Groups I and II showed adhesive failure. Conclusion: Within the limits of the study, 5% pentetic acid was as effective as 17% EDTA and hence can be considered as a potential chelating agent in endodontic therapy.